RANCANG BANGUN SISTEM INFORMASI DANA BOS BERBASIS WEB DI DINAS PENDIDIKAN PROVINSI JAWA TIMUR - Noveri Ikhsan; Arifin Puji Widodo; Teguh Sutanto (Jurnal Sistem Informasi Universitas Dinamika, 2017)
School Operational Assistance/Bantuan Operasional Sekolah (BOS) is a further development of the Social Safety Net (SSN) in Education, BOS is intended as a subsidy School Operational Cost to all learners of compulsory education. The Activity Budget Plan of School (RKAS) and quarterly fund usage report is needed to deliver the fund of BOS to school. When the school is late in delivering RKAS and fund usage report to the East Java Provincial Education Office, the BOS fund delivery and supervision of the BOS fund usage will not run smoothly.Based on these problems, The BOS Information Systems Based On Web is create. In this system there is an input form of RKAS reporting and input form quarterly reporting, and also the pages that provide information about the BOS fund for the school, and reminders for collecting the reports. If the school did not do the reporting, the system will send a warning messages to the school-related accounts.Conclusion of the trials that have been conducted, The BOS Information Systems able to produce three (3) reports which is RKAS reports, quarterly report and summary report that can be used by the head of BOS team of evaluation and supervision on the usage of the BOS fund.Key Words: Information System, BOS Funds, RKAS, Evaluation